2015
DOI: 10.1186/s12863-015-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale genetic analysis of the exploited Nile monitor (Varanus niloticus) in Sahelian Africa

Abstract: BackgroundOverexploitation of wildlife populations results in direct consequences, such as extinction and local extirpation, as well as indirect effects including genetic diversity loss and changes in genetic structure. A clear understanding of the underlying genetic patterns of harvested species is necessary for sustainable management. The Nile monitor (Varanus niloticus) is a commercially valuable species in the international leather industry, with the highest levels of exploitation concentrated throughout S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Additionally, the cryptic western lineage within V. niloticus exhibits genetic differentiation levels above those typically found between sister varanid species. In a fine-scale genetic analysis, Dowell et al (2015) similarly found a sharp genetic break between V. niloticus populations in western Mali and those farther east, with very little evidence of admixture despite no obvious current geographic barrier. The same study also found reduced genetic diversity levels within the western lineage compared to neighboring V. niloticus populations (Dowell et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the cryptic western lineage within V. niloticus exhibits genetic differentiation levels above those typically found between sister varanid species. In a fine-scale genetic analysis, Dowell et al (2015) similarly found a sharp genetic break between V. niloticus populations in western Mali and those farther east, with very little evidence of admixture despite no obvious current geographic barrier. The same study also found reduced genetic diversity levels within the western lineage compared to neighboring V. niloticus populations (Dowell et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…acanthurus (Fitch et al, 2005) following the modifications of Dowell et al (2015). Fragment analysis was carried out on an ABI 3100 Genetic Analyzer (Applied Biosystems, Inc.) with GeneScan 500 LIZ size standard and genotypes were scored using GeneMarker (SoftGenetics).…”
Section: Contemporary Sample Collection and Laboratory Protocolsmentioning
confidence: 99%
“…However, it seems very unlikely that a true interspeci c competition could occur between the two species as they remarkably differ in size and the area where they forage. Crocodiles entirely forage in aquatic habitats whereas Varanids prefer to both terrestrial and aquatic habitats with permanent water bodies to forage and open rooftops and streets to bask (Dowell et al 2015). Besides, Varanids inhabit a wide variety of habitats including woodland, dry savanna, scrub, evergreen thickets, swamps, mangroves, marshes, creeks, rivers, lakes and in disturbed areas near canals (Luiselli et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although the practice is not common in the Lake Tana Biosphere Reserve (LTBR), the species is being hunted in Sahelian Africa for its leather, food, pet trade and for some medical treatments (Ahmed et al 2018). Consequently, the species is listed under the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES, Appendix II) (Dowell et al 2015). This study, therefore, has tried to estimate population size, identify potential hotspots, and model the spatiotemporal distribution of Nile monitor (Varanus niloticus) within the LTBR, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Dowell et al (2015) examined the fine-scale genetic patterns of V. niloticus populations in West Africa under varying levels of exploitation pressure, and represents the only population-level assessment of native V. niloticus populations. For the four discrete populations that were inferred from microsatellite data, both genetic diversity and effective population size estimates were larger than for the introduced populations examined here, displaying H e values between 0.328 -0.429, and N e estimates ranging from 10.9 -1,327.27, depending on the population and method of analysis .…”
Section: Beach Populations (See Below)mentioning
confidence: 99%